Quantitative CT scans of lung parenchymal pathology in premature infants ages 0–6 years. Issue 3 (21st December 2017) - Spielberg, David R.; Walkup, Laura L.; Stein, Jill M.; Crotty, Eric J.; Rattan, Mantosh S; Hossain, Md Monir; Brody, Alan S.; Woods, Jason C.
Abstract: Background: Bronchopulmonary dysplasia (BPD) is a common, heterogeneous disease in premature infants. We hypothesized that quantitative CT techniques could assess lung parenchymal heterogeneity in BPD patients across a broad age range and demonstrate how pathologies change over time. Methods: A cross‐sectional, retrospective study of children age 0‐6 years with non‐contrast chest CT scans was conducted. BPD subjects met NICHD/NHLBI diagnostic criteria for BPD and were excluded for congenital lung/airway abnormalities or other known/suspected pulmonary diagnoses; control subjects were not premature and had normal CT scan findings. Radiologic opacities, lucencies, and spatial heterogeneity were quantified via: 1) thresholding using CT‐attenuation (HU); 2) manual segmentation; and 3) Ochiai reader‐scoring system. Clinical outcomes included BPD severity by NICHD/NHLBI criteria, respiratory support at NICU discharge, wheezing, and respiratory exacerbations. Results: Heterogeneity (standard deviation) of lung attenuation in BPD was significantly greater than in controls (difference 36.4 HU [26.1‐46.7 HU], P  < 0.001); the difference between the groups decreased 0.58 HU per month of age (0.08‐1.07 HU per month, P  = 0.02). BPD patients had greater amounts of opacities and lucencies than controls except with automated quantification of lucencies. Cross‐sectionally, lucencies per Ochiai score and opacities per manual segmentation decreased with time. No approach measured a statistically significant relationship to BPD clinical severity. Conclusions: Opacities, lucencies, and overall heterogeneity of lungs via quantitative CT can distinguish BPD patients from healthy controls, and these abnormalities decrease with age across BPD patients. Defining BPD severity by clinical outcomes such as respiratory support at several time points (vs a single time point, per current guidelines) may be meaningful.